Unstable ironies: narrative instability in Herman Charles Bosman's "Oom Schalk Lourens" series - Davis, Rebecca (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2006)
This thesis examines the narrative situation within Herman Charles Bosman's "Oom Schalk Lourens" series of stories, focussing on the nature of the relationship between author and narrator. In particular, it seeks to trace the source of the multiple ironies at work in the texts. It has been customary for critics in the past to claim that the irony within the stories stems from Bosman, operating authorially 'above' Oom Schalk. In terms of this theory, Oom Schalk is read as being largely unaware of the inconsistencies and contradictions within his narrative. It is the claim of this thesis, however, that Oom Schalk is the self-aware creator of the texts' ironies much of the time. Chapter 1 commences with an attempt at defining irony, and provides a brief overview of the history of its deployment within South African literature before discussing the literary genre which Bosman was to exploit as his ironic vehicle: the "oral-style" short story. Chapter 2 examines Wayne C. Booth's notions of "stable" and "unstable" irony: the irony of the Oom Schalk stories has, in the past, been classified as belonging to the former category, but this thesis attempts to show that its inconsistent deployment within the stories consigns it more accurately to the latter. Chapter 3 offers an assessment of the extrinsic contexts relevant to the analysis: the context of the stories' publication, and the likely composition of Bosman's reading public. Chapter 4 begins to examine the distance between implied author and implied narrator in the stories. Chapters 5, 6 and 7 subject stories dealing with the themes of art, race and land to detailed analysis in order to examine the shifting "“ and progressively, though unevenly, diminishing "“ distance between Bosman and Oom Schalk. The thesis concludes that the degree to which the ironic distance between author and narrator fluctuates within, and between, the stories, results in a narrative situation which must be classified as fundamentally unstable.
Keywords: Bosman, Herman Charles, 1905-1951 -- Criticism and interpretation; Irony in literature; Narration (Rhetoric)